Religious materiality in the early modern world - Ivanič, Suzanna; Laven, Mary; Morrall, Andrew (Visual and material culture, 1300-1700, 2019)
This edited volume is the first work to engage with religious materiality comparatively across the early modern world. It demonstrates how artefacts can provide their own bodies of material evidence about the nature of early modern religious practice and belief - and the nature of religious change - that can test, or even run counter to conventional, text-based narratives. Across twelve chapters this volume offers an unprecedented survey of early modern religious materiality in all its diversity. It brings together scholars of Catholic, Protestant, Jewish, Islamic and Buddhist practices from a range of areas of expertise, including history, art history, museum curatorship and social anthropology. At the same time, the volume emphasizes cultural encounter and exchange. In keeping with broader trends in the history of religion, the studies range from the use of objects prescribed by religious authorities to interactions with religious matter in the context of everyday lay beliefs.